2012
DOI: 10.1016/j.jacc.2011.07.053
|View full text |Cite
|
Sign up to set email alerts
|

A Dipeptidyl Peptidase-4 Inhibitor, Des-Fluoro-Sitagliptin, Improves Endothelial Function and Reduces Atherosclerotic Lesion Formation in Apolipoprotein E–Deficient Mice

Abstract: A DPP-4 inhibitor, DFS, exhibited antiatherogenic effects through augmenting GLP-1 activity in macrophages and endothelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
217
2
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 249 publications
(231 citation statements)
references
References 17 publications
9
217
2
3
Order By: Relevance
“…In addition, these agents have potential antiatherosclerotic properties. In a rodent model of atherosclerosis, GLP-1 and GLP-1 receptor agonists were reported to inhibit atherosclerosis and inflammation (6)(7)(8)(9), and DPP-4 inhibitors, including alogliptin, inhibit these pathological processes in GLP-1-dependent and -independent manners (10)(11)(12).…”
mentioning
confidence: 99%
“…In addition, these agents have potential antiatherosclerotic properties. In a rodent model of atherosclerosis, GLP-1 and GLP-1 receptor agonists were reported to inhibit atherosclerosis and inflammation (6)(7)(8)(9), and DPP-4 inhibitors, including alogliptin, inhibit these pathological processes in GLP-1-dependent and -independent manners (10)(11)(12).…”
mentioning
confidence: 99%
“…Recently, the DPP-IV inhibitors des-fluoro-sitagliptin and alogliptin have been shown to decrease atherosclerosis quantitatively in mouse studies [9,13]. However, little is known about the effects of DPP-IV inhibitors on plaque composition and on the stability of atherosclerotic plaques.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, sitagliptin, an oral glucose-lowering agent currently used for treating type 2 diabetes, has been found to enhance circulating glucagon-like peptide-1 (GLP-1) levels through inhibition of dipeptidyl peptidase IV (DPP-IV) activity [24,25] which, in turn, provides cardiovascular protection probably through the anti-inflammatory and anti-atherosclerotic activities of GLP-1 [26] . Additionally, our study recently demonstrated that sitagliptin therapy enhances stromal cell-derived factor (SDF)-1α level, numbers of endothelial progenitor cells (EPCs) in circulation, and angiogenesis through inhibition of DDP-IV in CD26 cells [27] .…”
mentioning
confidence: 99%